Reversing fortunes of German regions, 1926-2019: Boon and bane of early industrialization? - Paul Berbée; Sebastian Braun; Richard Franke (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
This paper shows that 19th-century industrialization is an important determinant of the significant changes in Germany's economic geography observed in recent decades. Using novel data on economic activity in 163 labor market regions in West Germany, we establish that nearly half of them experienced a reversal of fortune between 1926 and 2019, i.e., they moved from the lower to the upper median of the income distribution or vice versa. Economic decline is concentrated in North Germany, economic ascent in the South. Exploiting plausibly exogenous variation in access to coal, we show that early industrialization turned from an advantage for economic development to a burden after World War II. The dominant position of heavy industry, supported by the local political-administrative system, limited regional adaptability when the old industries fell into crisis. Today, the early industrialized regions suffer from low innovation and deindustrialization. The (time-varying) effect of industrialization explains most of the decline in regional inequality observed in the 1960s and 1970s and about half of the current north-south gap in economic development.
Keywords: N91; N92; O14; R12; 330; industrialization; economic development; regional inequality